Psychosocial Climate in the Classroom as a Factor in Academic Success: The Role of the Teacher–Student Relationship - Radojević, Tatjana S.; Kompirović, Tatjana P.; Ljajko, Šejla Š. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The question of the connection between the psychosocial climate in the classroom and student’s academic success is of great importance today, as the role of environment and social factors in the learning process is increasingly emphasized. Adequate research on this issue could illuminate the significant role of social and emotional aspects in education. The initial section of the paper presents terminological definitions of key concepts such as the psychosocial climate in the classroom, the teacher’s educational style, and student success. These definitions aim to provide a clearer picture of how different factors such as students’ attitudes towards the teacher, the classroom environment and the teachers’ educational styles can affect educational outcomes. The aim of this research was to examine the impact of the psychosocial climate on the academic success of elementary school students, with a particular focus on the social and emotional aspects of the school environment. The study included 111 students from fifth to eighth grade, from three elementary schools in the Gora municipality, in Kosovo and Metohija, using a descriptive-analytical method with a 26-item Likert scale. The research results showed that students place great importance on social and emotional factors such as the classroom atmosphere, relationships with teachers and peers, and parental support. Additionally, positive communication between teachers and students, as well as teachers’ educational styles play a significant role in fostering student motivation and academic success. It was found that democratic and permissive teaching styles have a positive effect on students while an authoritarian teaching style tends to negatively impact student autonomy and motivation. Thus, the results highlight the significant role of quality communication between teachers and students in creating a positive educational climate that directly influences academic success. The implications of this study suggest the need for developing a positive educational climate, which includes quality communication and appropriate teaching methods, to enhance motivation and improve students’ academic success.